Chelating the valley of death: Deferoxamine’s path from bench to wound clinic - Parker, Jennifer B.; Griffin, Michelle F.; Downer, Mauricio A.; Akras, Deena; Berry, Charlotte E.; Cotterell, Asha C.; Gurtner, Geoffrey C.; Longaker, Michael T.; Wan, Derrick C. (Frontiers in Medicine, 2023)
There is undisputable benefit in translating basic science research concretely into clinical practice, and yet, the vast majority of therapies and treatments fail to achieve approval. The rift between basic research and approved treatment continues to grow, and in cases where a drug is granted approval, the average time from initiation of human trials to regulatory marketing authorization spans almost a decade. Albeit with these hurdles, recent research with deferoxamine (DFO) bodes significant promise as a potential treatment for chronic, radiation-induced soft tissue injury. DFO was originally approved by the Food and Drug Administration (FDA) in 1968 for the treatment of iron overload. However, investigators more recently have posited that its angiogenic and antioxidant properties could be beneficial in treating the hypovascular and reactive-oxygen species-rich tissues seen in chronic wounds and radiation-induced fibrosis (RIF). Small animal experiments of various chronic wound and RIF models confirmed that treatment with DFO improved blood flow and collagen ultrastructure. With a well-established safety profile, and now a strong foundation of basic scientific research that supports its potential use in chronic wounds and RIF, the next steps required for DFO to achieve FDA marketing approval will include large animal studies and, if those prove successful, human clinical trials. Though these milestones remain, the extensive research thus far leaves hope for DFO to bridge the gap between bench and wound clinic in the near future.